Pengaruh Persepsi Kemudahan Penggunaan Aplikasi dan Digital Marketing terhadap Keputusan Pembelian Fore Coffee - Cahyadi, Nyoman Dewi Pitaloka; Sudewi, Ni Nyoman Dian; Yanthi, Ni Putu Dera; Febrianty , Putu Ayu Trisna; Devi N, I Gst. Ayu P. Jesika Sita (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
The industrial revolution has encouraged companies to adopt technology in their business operations. The purpose of this study is to examine the influence of perceptions of application usability and digital marketing on consumer purchasing decisions through applications. The study was conducted in the Denpasar area with a sample of 100 respondents. Data analysis in this study utilized multiple linear regression analysis. The results indicate that perceptions of app usability and digital marketing significantly influence consumer purchasing decisions through apps, both partially and simultaneously. Recommendations include that companies enhance app features and incorporate promotions within their apps.